MYTime: A Mindfulness and Yoga Program to Promote Health Outcomes in Parents of Children With Autism Spectrum Disorder - Leah R Ketcheson PhD; Carissa M Wengrovius PhD; Kerri L Staples PhD; Nancy Miodrag PhD (SAGE Publishing, 2022)
Background Parenting a child with Autism Spectrum Disorder can be stressful and result in health consequences for the caregivers, a population that is often overlooked and underserved. While mind-body interventions such as mindfulness yoga can help promote positive health outcomes, limited research has explored the impact of such a program on caregivers of children on the autism spectrum. Objective The primary objective of this pilot study was to evaluate the effects of a 12-week mindfulness yoga program (MYtime) on perceived stress, anxiety, and depression among urban caregivers of children on the autism spectrum. Methods Twenty-seven parents were randomized into either MYTime (n = 13) or the control group (n = 14). Perceived Stress Scale (PSS) and Depression, Anxiety, and Stress Scale (DASS) were administered. Results The MYTime group reported lower stress, depression and anxiety while the control group maintained similar scores across pre- and post-assessment. Following 12 weeks of participation the PSS and DASS scores improved by 25% and 49% respectively for parents in the MYTime group. In comparison, PSS scores worsened by 5% and DASS scores improved by 17% for the Control group. Differences in pre-and post-assessment scores were not significant for either group ( P > .05). Conclusion The results from this pilot study indicate that a mindfulness yoga program could be considered among feasible interventions aimed at improving the health of parents of children on the autism spectrum.